Efficacy of Essential Oils in Pain: A Systematic Review and Meta-Analysis of Preclinical Evidence - Scuteri, Damiana; Hamamura, Kengo; Sakurada, Tsukasa; Watanabe, Chizuko; Sakurada, Shinobu; Morrone, Luigi Antonio; Rombolà, Laura; Tonin, Paolo; Bagetta, Giacinto; Corasaniti, Maria Tiziana (Frontiers in Pharmacology, 2021)
Background: The demand for essential oils (EOs) has been steadily growing over the years. This is mirrored by a substantial increase in research concerned with EOs also in the field of inflammatory and neuropathic pain. The purpose of the present systematic review and meta-analysis is to investigate the preclinical evidence in favor of the working hypothesis of analgesic properties of EOs, hence elucidating whether there is a consistent rational basis for translation into clinic. Methods: A literature search has been conducted on databases relevant for medical scientific literature, i.e. PubMed/MEDLINE, Scopus and Web of Science from databases inception until November 2nd, 2020 following the PRISMA (Preferred Reporting Items for Systematic reviews and Meta-Analyses) criteria for systematic reviews and meta-analyses. Results: The search has been conducted to answer to the following PICOS (participants/population, interventions, comparisons, outcomes, and study design) question: are the EOs efficacious in reducing acute nociceptive pain and/or neuropathic pain in mice experimental models? It has retrieved 2491 records, leaving 954 studies to screen after duplicates removal. Title and abstract screening of 954 results has led to 127 records to evaluate in full text. Of these, 30 articles have resulted eligible for inclusion. Conclusions: Most studies (27) assess the analgesic properties of EOs on acute nociceptive pain models, e.g. the acetic acid writhings test, the formalin test and the hot plate test. Unfortunately, the efficacy in neuropathic pain models, more suitable to model human conditions of chronic pain, is poorly studied (in only 3 studies). Moreover, some methodologies can rise some concern in terms of risk of bias. Therefore, EOs with proven efficacy in both types of pain corroborated by methodologically consistent studies, like the EO of bergamot, should be studied in clinical trials, to enhance the translational impact of preclinical modelling on clinical pain research.